Recurrent Hydatid Cyst of Liver with Asymptomatic Concomitant Hydatid Cyst of Lung: An Unusual Presentation-Case Report - RANJAN, Ritesh (Iran J Parasitol, 2015)
A 40-year-old male patient presented to us with complaints of pain in abdomen for the past 2 weeks and fever for 3 days. The patient gave history of being previously operated for hydatid cyst of liver 15 years back. His chest radiograph and computed tomography scan revealed a cystic lesion in the right lobe of liver and a cyst in left lung. The patient was managed surgically. Aspirate from the cyst fluid showed plenty of hooklets and scolices of Echinococcus granulosus. An intact brood capsule was also seen. Diagnosis of hydatidosis was further confirmed by histopathological examination. Post-operative the patient had a good recovery.